PITI\/UNIJUÍ: quarentena domiciliar em tempos de pandemia - SANTOS DA ROSA BASSO , MICHELE; SCHONARDIE FILHO , LEOPOLDO; GLITZENHIRN BARRIQUELLO , FELIPE; RONCAGLIO , GABRIELI; JARDEL DALLABRIDA , MATEUS (Salão do Conhecimento, 2020)
Projeto de pesquisa e extensão do curso de Educação Física da UNIJUÍ/Ijuí